Pendampingan Usaha Rental Virtual Reality Untuk Pemberdayaan Ekonomi Multi-Sektor Di Desa Pilolalenga, Kabupaten Gorontalo - Dian Novian; Abd. Aziz Bouty; Ramlan Mustafa; Veggy Amran (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2025)
Digital economy penetration in rural areas remains limited despite diverse local economic potential. This community service program developed a Virtual Reality (VR) rental business as an innovative economic empowerment model in Pilolalenga Village, Gorontalo Regency. Using participatory action research approach over 8 weeks (August-September 2025), the program involved 60 villagers as pilot members. Activities included business feasibility assessment, infrastructure setup, technical orientation, business management mentoring, and continuous monitoring. Results showed VR rental business feasibility with 89.3% members achieving operational independence. Economic indicators revealed self-reported income increase of 27.3% (p=0.003) and market expansion of 234%. Learning effectiveness was demonstrated through large effect sizes (Cohen's d 1.29) across all modules. The business model projected break-even point within 12 weeks with monthly net profit of Rp 15.6 million. Twelve spontaneous cross-sector collaborative initiatives emerged organically. BUMDesa committed to continue operations independently with expansion target of 150 members within 12 months. This model demonstrates potential for replication in villages with adequate infrastructure.